Progress in Extrusion-Based Food Printing Technology for Enhanced Printability and Printing Efficiency of Typical Personalized Foods: A Review - Xiuxiu Teng; Chunli Li; Arun S. Mujumdar; Min Zhang (Foods, 2022)
Three-dimensional printing technology enables the personalization and on-demand production of edible products of individual specifications. Four-dimensional printing technology expands the application scope of 3D printing technology, which controllably changes the quality attributes of 3D printing products over time. The concept of 5D/6D printing technology is also gradually developing in the food field. However, the functional value of food printing technology remains largely unrealized on a commercial scale due to limitations of printability and printing efficiency. This review focuses on recent developments in breaking through these barriers. The key factors and improvement methods ranging from ink properties and printer design required for successful printing of personalized foods (including easy-to-swallow foods, specially shaped foods, and foods with controlled release of functional ingredients) are identified and discussed. Novel evaluation methods for printability and printing precision are outlined. Furthermore, the design of printing equipment to increase printing efficiency is discussed along with some suggestions for cost-effective commercial printing.